Shoulder injuries attributed to resistance training: A brief review - Kolber, M. J; Beekhuizen, K. S.; Cheng, M. -S. S.; Hellman, M. A. (The Journal of Strength and Conditioning Research, 2010)
The popularity of resistance training (RT) is evident by the more than 45 million Americans who engage in strength training regularly. Although the health and fitness benefits ascribed to RT are generally agreed upon, participation is not without risk. Acute and chronic injuries attributed to RT have been cited in the epidemiological literature among both competitive and recreational participants. The shoulder complex in particular has been alluded to as one of the most prevalent regions of injury. The purpose of this manuscript is to present an overview of documented shoulder injuries among the RT population and where possible discern mechanisms of injury and risk factors. A literature search was conducted in the PUBMED, CINAHL, SPORTDiscus, and OVID databases to identify relevant articles for inclusion using combinations of key words: resistance training, shoulder, bodybuilding, weightlifting, shoulder injury, and shoulder disorder. The results of the review indicated that up to 36% of documented RT-related injuries and disorders occur at the shoulder complex. Trends that increased the likelihood of injury were identified and inclusive of intrinsic risk factors such as joint and muscle imbalances and extrinsic risk factors, namely, that of improper attention to exercise technique. A majority of the available research was retrospective in nature, consisting of surveys and descriptive epidemiological reports. A paucity of research was available to identify predictive variables leading to injury, suggesting the need for future prospective-based investigations.